Psychometric validation of the SNAP-IV rating scale in amblyopic children at high AD/HD risk: structural validity and measurement invariance - Pan, Lu; Ru, Meng; Huang, Yuxing; Luo, Wuqiang; Li, Lili; Luo, Yan; Lin, Enwei; Kong, Min; Chen, Qi; Luo, Yali; Liu, Hairun; Huang, Siyan; et al. (Frontiers in Psychiatry, 2025)
ObjectiveTo validate the psychometric properties of the Swanson, Nolan, and Pelham Rating Scale (SNAP-IV) in amblyopic children at high AD/HD risk and establish its clinical utility for comorbid AD/HD screening.MethodsThis cross-sectional study utilized baseline data from the China Amblyopia Behavioral Cohort (CABC), which comprises 465 amblyopic children (aged 4–17 years). The reliability of the SNAP-IV was comprehensively assessed using Cronbach’s alpha and the split-half coefficient. The validity of the SNAP-IV was evaluated using criterion validity with the Conners’ parent rating scale (CPRS) and construct validity via confirmatory factor analysis (CFA). The measurement invariance of the SNAP-IV across gender and age groups was also investigated.ResultsThe SNAP-IV demonstrated exceptional internal consistency (Cronbach’s α = 0.965 [95% CI: 0.958–0.972], split-half coefficient = 0.891) and strong criterion validity with the CPRS domains, particularly with respect to the oppositional factor of the SNAP-IV scale, which showed the highest correlation with the conduct problem factor of the Conners’ Parent Rating Scale (CPRS) (rs = 0.837, 95% CI: 0.807–0.863, p<0.001, large effect). The findings indicated a substantial correlation between inattention and learning problems (rs = 0.808, 95% CI: 0.767–0.834, p<0.001, large effect) and conduct problems (rs = 0.719, 95% CI: 0.675–0.765, p<0.001, large effect). Confirmatory factor analysis confirmed a three-factor structure (inattention, hyperactivity/impulsivity, oppositional) with robust fit indices (χ²/(291) = 1033.4, χ²/df = 3.551, RMSEA=0.074, CFI=0.92, IFI=0.92), with full measurement invariance confirmed across gender and age groups.ConclusionsThis study constitutes the first systematic validation of the SNAP-IV in amblyopic children, thereby establishing its robustness for AD/HD screening in visually impaired populations. The scale’s standardized application has the potential to enhance the screening of early AD/HD-amblyopia comorbidity and the development of multidisciplinary intervention strategies for integrating visual and behavioral rehabilitation.